Textile-reinforced concrete as a structural member: a review - Venigalla, Sanjay Gokul; Abu Bakar, Nabilah; Mohd Nasir, Noor Azline; Safiee, Nor Azizi; Abd Aziz, Farah Nora Aznieta (Multidisciplinary Digital Publishing Institute, 2022)
Textile-reinforced concrete (TRC) is a form of reinforced concrete, where conventional reinforcement is replaced with textiles or fibers. The high tenacity of the textile fibers results in flexible and durable concrete structures. The literature has been limited to TRC applications in retrofitting and nonstructural applications. Therefore, this article attempts to detangle the progressive research direction on the usage of TRC as a structural member. For this, (i) a bibliometric study using scientometrics analysis to visualize the keyword network, and (ii) qualitative discussions on identified research areas were performed. The literature was categorized into four main research areas, namely material properties of TRC, composite behavior of TRC, bond-slip relations, and TRC applications as structural elements. In addition, the advantages and disadvantages in the usage of TRC as a structural member are discussed in association with the identified research areas. Furthermore, the article proposes future directions to reinforce the research on the usage of TRC as a structural element.